Cultural-Based Deviance on Islamic Law; Zakat Tekke Wale’ Spending in Basala, Konawe, Southeast Sulawesi, Indonesia - Kamaruddin; Misbahuddin; Suprijati Sarib; Syamsul Darlis (AL-IHKAM: Jurnal Hukum & Pranata Sosial, 2023)
Owners of swallow's nest in Basala District, South Konawe Regency give zakat of tekke wale' (swallow's nest) using gold zakat rate. This implies deviation from Islamic law and striking difference from the provisions of zakat law formulated by most Muslim scholars. This research aims to reveal the business phenomenon and practice of tekke wale' zakat spending, the factors beyond preference to use zakat with gold rate as well as culture-based deviations on Islamic law regarding this specific practice of zakat. This research is qualitative with an empirical-normative approach which includes interviews with swallow nest owners, community leaders, and religious leaders. Besides, it involves literature review to gather the data. The research shows that swallow nest business is a relatively new livelihood for local people so they have no definite guidance on how to spend the zakat. Their preference using gold zakat rate are due to five factors, ranging from lack of knowledge, assumption that swallow's nest is not a part of agricultural business, easy calculation in giving zakat using gold rate, following the previous swallow's nest owners, to easiness to determine the zakat recipients and spending period. Meanwhile, three forms of deviation from Islamic law existing at the practice urges the specific legal product concerning this specific commodity.